(untitled) (Bangladesh Journal of Agriculture, 2024)
A total of four root-knot nematode infected tomato root samples were collected from different locations in Gazipur, Bangladesh. Two methods of PCR were used to detect Meloidogyne spp. on tomatoes. One is molecular identification by DNA sequencing of the ribosomal DNA (rDNA) 28SD2/D3 gene, and another is PCR using species-specific SCAR primers. In the phylogenetic tree, the obtained sequences; OR351387, OR351388, OR351389, and OR351390 clustered with specific Meloidogyne incognita clade with a strong bootstrap support value of 100%. Species-specific primers produced a fragment of 399 bp for Meloidogyne incognita. Thus, utilizing species-specific markers and analyzing the results of a phylogenetic tree made from the amplified 28S D2/D3 gene region revealed the association of Meloidogyne incognita on tomato root-knot disease in Bangladesh. Bangladesh J. Agri. 2024, 49(1): 136-140